Effects of Wheat Flour and Baking Temperature on the Quality of Iranian Flat Bread-Part I: Physico-chemical Properties - AKRAM, A.; OMID, M.; GOLMOHAMMADI, A.; GHASEMI VARNAMKHASTI, M. (Asian Journal of Chemistry, 2010)
Information on the temperature of the environment in which the dough is produced as well as the temperature of oven are very important at different stages of preparing dough and baking bread. Three wheat cultivars and three baking temperatures (232, 249 and 260 °C) were used for baking samples of dough in an electric oven. Initially, physicochemical characteristics of Iranian flat bread made of three wheat cultivars is investigated. Thickness of dough after secondary proof, increase in bread volume, decrease in dough weight during baking and the duration of baking time were measured. Statistical analysis revealed that the effect of wheat cultivar on bread volume, decrease in dough weight during baking and baking time were statistically significant at the 1 % level. Maximum increase in bread volume dedicated to Chamran cultivar as 806.7 mL at 260 °C. Minimum decrease in dough weight was 15.26 g, related to Chamran cultivar at 260 °C, while the maximum was 38.93 g, in Pishtaz cultivar at the same temperature. Minimum and maximum baking times were 10 and 17 min, related to Chamran and Marvdasht cultivars at 260 and 232 °C, respectively.